The impact of payment and respondents’ participation on interviewers’ accuracy in face-to-face surveys: Investigations from a field experiment - Menold, Natalja; Landrock, Uta; Winker, Peter; Pellner, Nathalie; Kemper, Christoph J. (Field methods, 2018)
In face-to-face interviews, accurate work by interviewers is crucial for ensuring high-quality survey data. In a field experiment, payment of interviewers, legi...
Gesehen am 31.03.2020